2021
DOI: 10.3389/fmats.2021.728991
|View full text |Cite
|
Sign up to set email alerts
|

Slow Light Rainbow Trapping in a Uniformly Magnetized Gyromagnetic Photonic Crystal Waveguide

Abstract: We present a hybrid gyromagnetic photonic crystal (GPC) waveguide composed of different GPC waveguide segments possessing various cylinder radii and waveguide widths but biased by a uniform external magnetic field. We demonstrate in frequency and time domains that based on the strong coupling of two counter-propagating topologically protected one-way edge states, the intriguing slow light rainbow trapping (SLRT) of electromagnetic (EM) waves can be achieved, that is, EM waves of different frequencies can be sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…To attack this issue, in 2021, Chen et al presented a novel scheme to realize a slow-light rainbow trapping in a waveguide channel consisting of hybrid GPCs, which are of distinct geometric configurations but immersed in a uniform external magnetic field. [91] Besides, they also demonstrated that the slow-light rainbow trapping can be remotely and nonreciprocally controlled. These results show that in GPC waveguide system, the strong coupling between two TPSs can be apparently and arbitrarily regulated by a series of means, such as modulating the radius of gyromagnetic cylinder and the width of waveguide channel, tuning the direction and intensity of external magnetic field.…”
Section: Strong Coupling Between Two Chiral One-way Edge Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…To attack this issue, in 2021, Chen et al presented a novel scheme to realize a slow-light rainbow trapping in a waveguide channel consisting of hybrid GPCs, which are of distinct geometric configurations but immersed in a uniform external magnetic field. [91] Besides, they also demonstrated that the slow-light rainbow trapping can be remotely and nonreciprocally controlled. These results show that in GPC waveguide system, the strong coupling between two TPSs can be apparently and arbitrarily regulated by a series of means, such as modulating the radius of gyromagnetic cylinder and the width of waveguide channel, tuning the direction and intensity of external magnetic field.…”
Section: Strong Coupling Between Two Chiral One-way Edge Statesmentioning
confidence: 99%
“…To further explore the rich physics, novel properties, and potential applications of TPSs in GPCs, many functionalities and prototypes of photonic devices derived from the interactions between TPSs have been presented in recent years, e.g., topological dispersionless slow light, [87,88] switchable slow light rainbow trapping, [89] and other functionalities. [90][91][92] It has been gradually understood and appreciated that the GPCs possess three unique advantages for investigating the interactions between TPSs: (i) each edge supports the single-mode one-way edge states, which is conducive to realize the coupling between TPSs of distinct configurations; (ii) it can produce imperfect localized edge states so that each GPC can couple part of energy fluxes of another GPC to its own edge and propagate forwards; (iii) the transport directions of one-way edge states can be tuned by reversing the external magnetic field, so distinct coupling types between TPSs can be constructed in one GPC system. Here we will mainly give a brief introduction to review two typical configurations, i.e., the coupling between two co-propagating chiral one-way edge states or two counter-propagating chiral one-way edge states in GPC waveguides, and discuss the related physical phenomena and functional applications resulting from these coupling effects.…”
Section: Strong Coupling Between Two Chiral One-way Edge Statesmentioning
confidence: 99%
“…Tapered magnetic fields in nonreciprocal waveguides has been proposed to achieve rainbow trapping with fully stopped light 28 . These designs involved the use of gyromagnetic materials 29 or an external magnetic field 30 , significantly increasing system complexity. Recently, some advances were made toward topological rainbow effects 31 37 based on the topological photonics theory via controlling the group velocities of topological photonic states.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired from the discovery of condensed quantum Hall effect, many studies have shown that topological states show essentially single-particle behavior of electrons and one can establish an analogy relationship with photon behaviors called topological photonic state (or topological one-way edge state) [4][5][6][7]. Topological one-way edge state provides a powerful platform for novel photonic devices with nontrivial functionalities and excellent performances, such as one-way waveguide [8][9][10][11][12], topological laser [13][14][15][16][17], rainbow trapping phenomenon [18][19][20][21], dispersionless slow light [22][23][24], topological fibre [25][26][27].…”
Section: Introductionmentioning
confidence: 99%